2022
DOI: 10.1002/ange.202202519
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional WC‐Supported RuO2 Nanoparticles for Robust Water Splitting in Acidic Media

Abstract: We report the strong catalyst–support interaction in WC‐supported RuO2 nanoparticles (RuO2‐WC NPs) anchored on carbon nanosheets with low loading of Ru (4.11 wt.%), which significantly promotes the oxygen evolution reaction activity with a η10 of 347 mV and a mass activity of 1430 A gRu−1, eight‐fold higher than that of commercial RuO2 (176 A gRu−1). Theoretical calculations demonstrate that the strong catalyst–support interaction between RuO2 and the WC support could optimize the surrounding electronic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…From the SEM and TEM analyses, it was concluded that the heterojunction interface between the Bi 4 TaO 8 Br nanoplates and CdS QDs was formed, and this kind of 0D/2D heterojunction is beneficial to the improvement of photocatalytic activity because of the optimized charge separation efficiency and exposed active sites. 36,37 The interior interactions of different compositions in the as-prepared specimens were scrutinized via XPS technology. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From the SEM and TEM analyses, it was concluded that the heterojunction interface between the Bi 4 TaO 8 Br nanoplates and CdS QDs was formed, and this kind of 0D/2D heterojunction is beneficial to the improvement of photocatalytic activity because of the optimized charge separation efficiency and exposed active sites. 36,37 The interior interactions of different compositions in the as-prepared specimens were scrutinized via XPS technology. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations suggested that the interaction between WC and RuO 2 could optimize the adsorption energy of Ru sites for the intermediate species of the OER process to reduce the reaction barrier (Figure 6g). 41 Meanwhile, the electron-donating effect of WC can reduce the oxidation degree of Ru active sites. Therefore, WC-supported RuO 2 nanoparticles (NPs) anchored on carbon NSs can be efficient and stable acidic OER catalysts (Figure 6h,i).…”
Section: Interface Engineeringmentioning
confidence: 99%
“…In addition, we also investigated the function of support–catalyst effect in the RuO 2 –WC system. DFT calculations suggested that the interaction between WC and RuO 2 could optimize the adsorption energy of Ru sites for the intermediate species of the OER process to reduce the reaction barrier (Figure g) . Meanwhile, the electron-donating effect of WC can reduce the oxidation degree of Ru active sites.…”
Section: Regulation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, common OER catalytic systems include various oxides (metal oxides, perovskite oxides, spinel oxides, hydroxides, and other oxides), nonoxides (metal sulfides, metal selenides, metal phosphides, metal nitrides, and metal carbides), and carbon-based catalysts (graphene, carbon nanotubes, and others). Among them, one of the important OER catalysts is metal oxides (see Scheme ). Some precious metal oxides such as RuO 2 , IrO 2 , etc., exhibit a high OER catalytic activity, which is regarded as a benchmark of the OER catalyst development in alkaline and acidic electrolytes. However, the stabilities of RuO 2 and IrO 2 are insufficient at high anodic potentials, resulting in a decrease in the OER catalytic performance, and their high costs and low reserves limit their wide application in industrial scalability as catalysts for OERs. Therefore, it is very important to develop and design low-cost, efficient, and stable OER catalysts.…”
Section: Introductionmentioning
confidence: 99%